Periodicity and Modernity in the Principles of Sports Management - M. Mamatov (European Journal of Life Safety and Stability (2660-9630), 2023)
This article highlights the content of the principles of sports management, its historicity and rationality, the transformation of the relationship of functionality by continuity and the trend of its change in the process of globalization.